Genetic variability, combining ability, and stability analysis studies on traditional okra genotypes and their hybrids (Abelmoschus esculentus (L.) Moench) using line × tester design - R. Praviinkumar; P. Nishok; R. Vignesh; M. Harini; N. Senthilkumar (Рослинництво та ґрунтознавство, 2024)
Improving fruit yield in traditional okra varieties is vital for food security, sustainable agriculture, and the conservation of landrace diversity. Evaluating their genetic potential and stability with modern testers is key to achieving higher yields and advancing crop improvement. The study aimed to assess the genetic variability, combining ability, gene action, and stability of traditional okra genotypes and their hybrids using a line × tester design to identify high-yielding, stable hybrids with specific environmental adaptability and enhanced fruit yield. A line × tester analysis was conducted during the period 2022-2024 at Annamalai University, Chidambaram (India), using seven lines and three testers to investigate combining ability, gene action, and heterosis in traditional okra genotypes (Abelmoschus esculentus (L.) Moench). The parents were selected from a diverse group of 32 traditional landraces. The study evaluated ten economically important traits, including days to 50% flowering, plant architecture, and yield components. Combining ability analysis indicated the predominance of nonadditive gene action for all traits studied. Among the parents, Heirloom White, Anchita Local (lines), and Arka Anamika (tester) exhibited superior general combining ability for multiple traits, including fruit yield. The crosses Green Long Okra × Arka Anamika and Anchita Local × Arka Anamika emerged as superior hybrids, demonstrating significant specific combining ability effects and desirable standard heterosis for fruit yield and its component traits. AMMI analysis confirmed these hybrids’ environmental adaptability, with Anchita Local × Arka Anamika showing particular stability across environments. Strong correlations were observed between yield components, notably between fruit dimensions and yield per plant. The high heritability combined with the prevalence of nonadditive gene action suggests that hybrid breeding would be more effective than pure line selection for crop improvement. These findings provide valuable insights for okra breeding programmes aimed at developing high-yielding, stable hybrids with specific adaptation